Sensitivity of Human Erythrocytes to Posthypertonic Shock in Glycerol Presence - Chabanenko, Olena O.; Shpakova, Natalia M.; Orlova, Natalia V. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 183